2020
DOI: 10.1371/journal.ppat.1008251
|View full text |Cite
|
Sign up to set email alerts
|

CFTR dysregulation drives active selection of the gut microbiome

Abstract: Patients with cystic fibrosis (CF) have altered fecal microbiomes compared to those of healthy controls. The magnitude of this dysbiosis correlates with measures of CF gastrointestinal (GI) disease, including GI inflammation and nutrient malabsorption. However, whether this dysbiosis is caused by mutations in the CFTR gene, the underlying defect in CF, or whether CF-associated dysbiosis augments GI disease was not clear. To test the relationships between CFTR dysfunction, microbes, and intestinal health, we es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 48 publications
(71 reference statements)
8
71
0
Order By: Relevance
“…Preclinical animal models are a prerequisite to test therapeutic strategies targeting the gut microbiomes of CF patients. To date, almost all CF animal gut microbiome studies have used mice [ 16 , 17 , 18 ]. Interestingly, loss of functional CFTR in CF mice is associated with significant decreases in GI bacterial community richness, evenness, and diversity, and reduced relative abundance of putative protective species in some reports [ 16 ], but not in others [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical animal models are a prerequisite to test therapeutic strategies targeting the gut microbiomes of CF patients. To date, almost all CF animal gut microbiome studies have used mice [ 16 , 17 , 18 ]. Interestingly, loss of functional CFTR in CF mice is associated with significant decreases in GI bacterial community richness, evenness, and diversity, and reduced relative abundance of putative protective species in some reports [ 16 ], but not in others [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal tract involvement in CF begins during fetal life and is noted in most patients [ 2 , 32 ]. Associated common GI symptoms in CF include abdominal pain, bloating, distention, steatorrhea, poor weight gain, and constipation [ 2 , 33 ]. CFTR is expressed in intestinal epithelial cells, and its dysfunction in CF results in defective CFTR protein, which leads to various physiological and biochemical imbalances.…”
Section: Gut Dysbiosis In Cystic Fibrosismentioning
confidence: 99%
“…These include thick and inspissated mucus due to chloride channel dysfunction, defective bicarbonate secretion altering the intestinal pH milieu, prolonged intestinal transit, pancreatic insufficiency, enhanced intestinal inflammation, and altered immune mechanisms with an impaired intestinal barrier function [ 9 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] ( Table 2 ). Clinically, the GI symptoms in CF are mainly related to obstruction, malabsorption, and inflammation [ 2 , 33 ]. The changes in the GI ecosystem result in an early and chronic state of gut dysbiosis.…”
Section: Gut Dysbiosis In Cystic Fibrosismentioning
confidence: 99%
“…Lynch et al demonstrated that changes in CF and non-CF mouse microbiome under antibiotics were greater than the pre-treatment difference between the two types of mice [65]. Germ-free animals [66] or animals under different diets [67] are other ways to explore microbiome function. Finally, animal models can explore the gut-lung axis or specific microbial interactions identified as pathophysiologically critical by -omics studies [68].…”
Section: Animal Modelsmentioning
confidence: 99%
“…A close relationship was demonstrated between cftr genotype and microbiome constitution [66]. CF mice initially germ-free and transplanted with fecal microbiota from non-CF mice had a different microbiological profile than non-CF controls [66]. However, the exact mechanisms of microorganism selection by genotype are unknown.…”
Section: Influence Of Cftr Mutation On Pulmotypes and Enterotypesmentioning
confidence: 99%